Recurrent bladder urothelial carcinoma complicated with primary bladder large cell neuroendocrine carcinoma: a case report and literature review - Cui, Jiarui; Zhao, Qing; Yu, Chunhong; Ma, Pengfei; Li, Shoubin (Frontiers in Oncology, 2024)
Objective To improve the understanding, diagnosis and treatment of bladder large cell neuroendocrine carcinoma (LCNEC). Methods A clinical case of bladder LCNEC admitted to our hospital was reported. The epidemiology, prognosis, diagnosis and treatment methods of large cell neuroendocrine carcinoma were reviewed. The diagnosis and treatment status and prognosis were discussed based on the literature. Results The female patient was admitted to hospital for "more than 4 years after TURBT and intermittent hematuria for more than 2 years". She was diagnosed as recurrent bladder cancer and underwent "radical cystotomy + hysterectomy". The postoperative pathological findings were high-grade urothelial carcinoma of the bladder neck and large cell neuroendocrine carcinoma of the bladder. The patient recovered well after surgery, but refused radiotherapy and chemotherapy and is still under close follow-up. Conclusion Bladder LCNEC is clinically rare, has unique pathological features, is more aggressive than traditional urothelial carcinoma, and has a poor prognosis. Surgery, chemotherapy and radiotherapy should be combined with multi-mode treatment.